To assess and compare the mental health of current-left-behind children, previous-left-behind children with never-left-behind children - Yang, Guangyan (Frontiers in Public Health, 2022)
The study's goal was to compare the mental health of children who are now left behind (current-LBC) to children who have never been left behind (never-LBC). Recruits were culled from rural Chinese schools. The Strengths and Difficulties Questionnaire (SDQ) and the Parent–Adolescent Communication Scale (PACS) were used to examine participants' migratory status, mental health, and parent-child communication (PACS). A total of 2000, current-, 500 previous-, and 300 never-LBCs in had complete data readily accessible for research and analysis. A number of mental health issues, such as emotional symptoms, conduct and hyperactivity issues as well as overall challenges were considerably increased when all confounding factors were taken into account in the analysis. Our findings also showed a substantial link between children's overall issues and their inability to effectively communicate with parents. Children suffer long-term consequences as a result of their parents' frequent moves. The mental health of children is closely linked to the quality of communication between parents and children. Migrant parents' ability to comprehend and communicate with their children is critical to their children's development, according to the findings of this study.